Dynamic MTORC1-TFEB feedback signaling regulates hepatic autophagy, steatosis and liver injury in long-term nutrient oversupply. Issue 10 (3rd October 2018) - Zhang, Hao; Yan, Shengmin; Khambu, Bilon; Ma, Fengguang; Li, Yong; Chen, Xiaoyun; Martina, Jose. A.; Puertollano, Rosa; Li, Yu; Chalasani, Naga; Yin, Xiao-Ming
ABSTRACT: Normal metabolism requires a controlled balance between anabolism and catabolism. It is not completely known how this balance can be retained when the level of nutrient supply changes in the long term. We found that in murine liver anabolism, as represented by the phosphorylation of RPS6KB (ribosomal protein S6 kinase), was soon elevated while catabolism, as represented by TFEB (transcription factor EB)-directed gene transcription and lysosomal activities, was downregulated after the administration of a high-fat diet (HFD). Surprisingly, neither the alteration in RPS6KB phosphorylation nor that in TFEB functions was static over the long course of HFD feeding. Instead, the 2 signals exhibited dynamic alterations in opposite directions, which could be explained by the dependence of MTORC1 (MTOR complex 1) activation on TFEB-supported lysosome function and the feedback suppression of TFEB by MTORC1. Disruption of the dynamics by enforced expression of TFEB in HFD-fed mice at the peaks of MTORC1 activation restored lysosome function. Consistently, interference of MTORC1 activation with rapamycin or with a constitutively activated RRAGA mutant at the peak or nadir of MTORC1 oscillation enhanced or reduced the lysosome function, respectively. These treatments also improved or exacerbated hepatic steatosis and liver injury, respectively. Finally, there was a significant inverse correlation between TFEB activation and steatosis severity in the livers of patients with non-alcohol fatty liver diseases, supporting the clinical relevance of TFEB-regulated events. Thus, maintaining catabolic function through feedback mechanisms during enhanced anabolism, which is caused by nutrient oversupply, is important for reducing liver pathology.